A Cost-Effective Method for Preparing Robust and Conductive Superhydrophobic Coatings Based on Asphalt. (24th December 2020) - Li, Wenbin; Wang, Yong; Feng, Yanting; Wang, Qing; Xu, Xuexia; Li, Guowei; Dong, Guozhen; Jing, Shangqian; Chen, Ersong; Fan, Xiaoliang; Wang, Peng
Abstract : The wide application of superhydrophobic materials is mainly hindered by the poor mechanical robustness and complicated preparation method. To overcome these problems, we tried to make a combination of hierarchical and self-similar structure by the means of a simple spraying method. By adding nanofiller (carbon nanotube) and microfiller (graphite powder and expanded graphite), the hierarchical structure was constructed. By further doping the fillers in the commercial asphalt uniformly, the self-similar structure was prepared. Based on the aforementioned work, the as-prepared sample could withstand the sandpaper abrasion for 12.00 m under 4.90 kPa. Moreover, this superhydrophobic coating demonstrated good conductivity, superior self-cleaning property, and excellent corrosion resistance. The integration of conductivity with the superhydrophobicity might open new avenues for ground grid applications.